KREDIT DAN MODAL SOSIAL DALAM PERSPEKTIF TEORI DAN PRAKTEK - LALU MUH. KABUL; OKKY AFRIWAN (Universitas Mahasaraswati K. Mataram, 2021)
The aim of the study is to analyze credit markets and social capital based on theoretical and practical perspectives. The study method used is descriptive. The result of study showed that theoretically, asymmetric information problem can’t be solved by bank, therefore collateral is needed as a requirement for credit landing. Others, the collateral has an implication to bad performance of borrower business activities, thus high credit default occures. Embedded of social capital in group can solved the asymmetric information problem and highly credit default. Therefore, collateral is not needed again in developing link between group and bank. Existing of social capital is not only in group, but also in cooperative institutions. Practically, low level of credit default in cooperative institution sample related with embedded of social capital in the cooperative institution.